A Refined Nomenclature System to Better Discriminate Endo- and Exo-Type Fructanases and Glucanases - Laura Leaerts; Jaime Ricardo Porras-Domínguez; Maxime Versluys; Wim Van den Ende (Biomolecules)
Distinguishing between endo- and exo-type enzymes within the glycoside hydrolase (GH) classification presents significant challenges. Traditional methods, often based on endpoint activity measurements, do not capture the full range of products generated, leading to inconsistencies in classification. Not all exo-acting fructanases and glucanases produce monosaccharides (like fructose or glucose), while endo-acting enzymes do not solely produce higher-degree polymerization oligosaccharides. In practice, both enzyme types can yield a variety of products throughout the reaction, complicating classification efforts. To address these challenges, we propose a refined nomenclature system for GH enzymes, including fructanases and glucanases, based on good practices and initial product formation. This system classifies enzymes into four categories for each type: Fr, Fn, Fn,n+1 and F1 for fructanases, and Gr, Gn, Gn,n+1 and G1 for glucanases, based on their mode of action (endo- or exo-based) and initial product profiles. Our refined nomenclature system will advance enzyme structure–function research and support the production and application of fructan and glucan oligosaccharides as prebiotics, priming agents, and potential signaling molecules in microbe–microbe and plant–microbe interactions. Ultimately, this system could benefit agronomy and the food industry, contributing to health improvements.